2021
DOI: 10.3847/2041-8213/ac2957
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Polar Terrestrial Circumbinary Planets

Abstract: All circumbinary planets (CBPs) currently detected are in orbits that are almost coplanar to the binary orbit. While misaligned CBPs are more difficult to detect, observations of polar-aligned circumbinary gas and debris disks around eccentric binaries suggest that polar planet formation may be possible. A polar-aligned planet has a stable orbit that is inclined by 90° to the orbital plane of the binary with an angular momentum vector that is aligned to the binary eccentricity vector. With n-body simulations w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The different binary models and their corresponding binary eccentricities are listed in Table 1 and are marked by red triangles in Figure 1. The initial surface density profile is taken to be that of a steady circumbinary gas disk as described in Childs & Martin (2021b). At least initially, both particle disks around the circular orbit binary are in circulating orbits while around the eccentric orbit binary they are librating.…”
Section: Terrestrial Circumbinary Planet Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The different binary models and their corresponding binary eccentricities are listed in Table 1 and are marked by red triangles in Figure 1. The initial surface density profile is taken to be that of a steady circumbinary gas disk as described in Childs & Martin (2021b). At least initially, both particle disks around the circular orbit binary are in circulating orbits while around the eccentric orbit binary they are librating.…”
Section: Terrestrial Circumbinary Planet Formationmentioning
confidence: 99%
“…Coplanar and polar circumbinary orbits are stationary states in which the particles do not undergo significant nodal precession. As a result, terrestrial planets can efficiently form in coplanar (Quintana & Lissauer 2006;Childs & Martin 2021a) and polar aligned (Childs & Martin 2021b) circumbinary disks through core accretion. Such terrestrial circumbinary planets (CBPs) have yet to be observed, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissipation within the disk causes the disk to align towards coplanar to the binary orbit, or polar to the binary orbit and aligned to the binary eccentricity vector Lubow & Martin 2018;Zanazzi & Lai 2018). While all currently detected circumbinary planets are in coplanar orbits, around an eccentric binary polar planets may be more stable than coplanar planets (Chen et al 2020) and terrestrial planets at least form more efficiently (Childs & Martin 2021). If the disk lifetime is shorter than the disk alignment timescale then planets may form in misaligned orbits.…”
Section: Introductionmentioning
confidence: 99%
“…Zanardi et al (2018) examined the effects of GR on the orbit of an asteroid around a star with an inner eccentric orbit planet. Childs & Martin (2021) found that general relativity (GR) does not affect the dynamics of very close in (orbital radius r < 4 au) terrestrial planets around a 0.5 au semi-major axis binary since the planet orbits precess with the binary and remain polar aligned.…”
Section: Introductionmentioning
confidence: 99%